Clinical and haematological changes upon administration of Xylazine-Ketamine and Xylazine-Thiopentoneanaesthetic combinations in ewes (Bangladesh Veterinarian, 2018)
The study was done to evaluate the effect of Xylazine-Ketamine and Xylazine- Thiopentone combinations for general anaesthesia in sheep. Six healthy sheep were divided into two groups: Group XK (n = 3), anaesthetized with Xylazine-Ketamine and Group XT (n = 3), anaesthetized with xylazine-thiopentone. Anaesthesia was induced using 1.1 mg/kg xylazine with 10 mg/kg ketamine or 20 mg/kg thiopentone as a single intravenous injection. Induction, duration and recovery from anaesthesia were monitored. Respiratory rate, heart rate and rectal temperature were recorded 15 min before and 5 min after induction, and 15 and 30 min and 24 hours after recovery. Packed Cell Volume (PCV) (%), Haemoglobin (Hb) (g/dL), Total Leucocyte Count (TLC) (millions per cubic millimetre) and Total Erythrocyte Count (TEC; Thousands per cubic millimetre) were measured before anaesthesia, one hour after induction and 24 hours after recovery. Heart rate increased significantly in both XT and XK groups and returned to control value 24 hours after recovery. Respiration rate decreased at 15 min after induction, then highly increased at 30 min and then returned to control value 24 hours after recovery in XK group. Rectal temperature decreased significantly in both groups. Hb, TLC, and TEC decreased, but PCV increased significantly in both groups. The mean time of induction of anaesthesia was less in XT group (0.2 ± 0.0 min) than in group XK (2.7 ± 0.1 min). The duration of anaesthesia and its recovery was less in Group XK than in Group XT. A combination of Xylazine-Ketamine and Xylazine-Thiopentone can be used to induce short term anaesthesia in sheep with negligible effects on clinical and haematological parameters.Bangl. vet. 2017. Vol. 34, No. 1, 9-19